PROMOTING MULTICULTURAL EDUCATION THROUGH CULTURALLY RESPONSIVE TEACHING IN CITIES AND VILLAGES: UNDERSTANDING THE DIFFERENCES AND IMPLICATIONS FOR EDUCATORS - M. Inzah (HUMANISTIKA : Jurnal Keislaman, 2023)
Multicultural education is an approach to teaching and learning that recognizes and values the diversity of students' backgrounds, experiences, and perspectives. However, the implementation of multicultural education may differ in cities and villages due to differences in population, resources, and cultural norms. This paper explores the differences in multicultural education in cities and villages, and their implications for educators. Drawing on literature from many resources of scientific paper, the paper highlights the challenges and opportunities for multicultural education in both urban and rural settings.